ANALYSIS OF LEGAL STATUS, LEGAL PROTECTION OF MARKS THAT HAVE BEEN REGISTERED (STUDY OF DECISION NUMBER 03/PDT.SUS-MEREK/2015/PN NIAGA MEDAN) - Lenny Mutiara Ambarita; Van Lodewijk Purba; Muhammad Fadly Nasution (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The purpose of this study is to analyze the legal position and legal protection of trademarks that have been registered (Study of Decision Number 03/Pdt.Sus-MEREK/2015/PN Niaga Medan). The type of research used in writing this thesis is normative juridical research. Normative juridical research, "is a research conducted by examining literature or secondary data such as laws and regulations, legal theory, and opinions of leading legal scholars". The data used as material for the analysis of this thesis research is secondary data, namely the data in this study consists of primary legal materials, secondary legal materials and tertiary legal materials. The analysis was carried out by means of qualitative analysis, namely an analysis that uses normative (juridical) aspects through a method that is descriptive in nature, an analysis that describes an overview of the legal materials obtained and links them to one another to obtain a general conclusion. The results of the study show that in a constitutive system, the legal protection of trademark rights is based on the registration of a mark (first to file system). Whoever registers a mark for the first time and is accepted, the applicant has the most right to a mark because registration creates rights to a mark, so that a mark is protected by law, the mark must be registered by the owner. In addition, it is also necessary to pay attention to the reputation of a well-known brand that is obtained due to vigorous and large-scale promotions, investment in several countries in the world made by the owner and accompanied by proof of registration of the mark in several countries. The law in Indonesia does not protect the first mark user, but the law protects the first mark registrant. Mark Registration is a must in order to obtain rights to a mark. Without registration, the state will not grant trademark rights to brand owners.